Lack of association between CD28 IVS3+ 17T/C SNP and the susceptibility to SLE in the Malaysian population - Lau, T.P.; Lian, L.H.; Puah, S.M.; Chew, C.H.; Tan, S.Y.; Chua, Kek Heng (Malaysian Society for Molecular Biology and Biotechnology, 2008)
Systemic Lupus Erythematosus (SLE) is a generalized autoimmune disease which results in multiorgan damage. The pathogenesis of SLE is mainly due to the over-production of autoantibodies and immune complexes, as well as abnormal regulation of their production and clearance. One of the many factors that lead to the over-production of autoantibodies is the hyperactivity of T- and B-cells. Owing to the costimulatory function of the CD28 molecule during T-cell activation, the CD28 gene is the target of our study. The results show that the T allele of the CD28 gene and its corresponding homozygous genotype scored the highest frequency amongst the Malaysian population. However, the CD28 gene is not significantly associated with the susceptibility of SLE when comparing between diseased and normal healthy subjects.